Trade Openness and Economic Growth in Nepal - Rana, Surya Bahadur (Butwal Campus Journal, 2020)
This study examines the impact of trade openness on economic growth in Nepal over the period 1975-2019. Using ARDL bounds testing approach to co integration in the multivariate framework, the study results reveal that there exists a long-run relationship between Nepal’s foreign trade and economic growth over the study period. The long-run estimates of ARDL models how that the level of trade openness in Nepal predicts the rate of economic growth of the country positively and significantly in the long-run. The study also reports the positive and significant long run effect of investment level on growth in Nepal over the study period supporting the trade induced investment growth hypothesis. It postulates that trade openness affects economic growth through the channel of investment. The growth enhancing role of trade openness implies that Nepal Government should promote international trade by eliminating trade barriers and making the procedures of foreign trade simple and convenient. Besides, Nepal’s import policy should promote investment environment particularly in capital intensive sectors to take the advantage of technology transfer from technologically advanced country. Furthermore, Nepal should pay proper attention and come up with effective human resource development policy that can uplift human knowledge and skills to make use of technologies from developed countries.